Intrasphenoidal cephalocoeles: Knowing the less known - Prachi Mann; Sanjog S. Gajbhiye; Deoyani Sarjare; Aarti Anand; Shrikant Kalbagwar; Pramod Giri (South African Journal of Radiology, 2024)
Intrasphenoidal encephalocoeles are acquired or congenital herniations of meninges and brain parenchyma through a structural sphenoid bone defect. Acquired causes are most common, either iatrogenic, post-traumatic, or spontaneous. However, defects in the lateral wall of the sphenoid sinus are uncommon and cephalocoeles through them relatively underexplored in current literature, warranting dedicated attention to unravel their complexities. Congenital causes such as persistence of Sternberg’s canal, which can lead to lateral cephalocoeles, is a rare entity, seen in two of the presented cases, based on the location of the defect with respect to the line connecting the foramen rotundum and the vidian canal (VR line). Three cases of intrasphenoidal cephalocoeles are presented; two patients presented with watery nasal discharge without prior trauma or surgery and the third case was incidentally detected in an elderly patient with intraparenchymal haemorrhage. Imaging with CT cisternography and brain MR were performed to ascertain the exact location of the leak and confirm the presence of herniated brain tissue via the defects. Patients were evaluated by otolaryngology for transnasal endoscopic repair, which was deemed unfeasible, and referred to neurosurgery for transcranial duroplasty.